Pengaruh Suplemen Organik Terhadap Regenerasi Tunas Pisang Barangan Musa acuminata Colla. Secara In Vitro - Tuwo, Mustika; Baharuddin, Baharuddin; Latunra, Andi Ilham; Masniawati, A.; Kuswinanti, Tutik (Metamorfosa: Journal of Biological Sciences, 2021)
The research purpose to know ability of natural supplements in supporting the regeneration of banana cv. Barangan Musa acuminata Colla.  Explants were cultured on MS basal medium (control) with natural supplements: coconut water (CW) 5; 10; 15 and 20%, green bean sprout extract (GBSE) and sweet corn extract (SCE) at 50; 100; 150 and 200 g/l. After 4 weeks of cultivation, maximum multiplication shoots (7.11 ± 0.19), shoot length (2.00 ± 0.22), and number of leaves (4.00 ± 0.38) was obtained in MS + 200 g/l bean sprout extract. The addition of natural supplements to the medium showed better results on all parameters of observation than control. This results indicates the potential of natural supplements for supporting of Barangan Musa acuminata Colla. propagation in vitro culture.